Androgens as adjuvant treatment in postmenopausal female patients with rheumatoid arthritis. - Booji, A (1996)
OBJECTIVE: To examine the possible beneficial effect of androgens in postmenopausal women with active rheumatoid arthritis. METHODS: 107 women participated in a double blind placebo controlled trial to evaluate the effect of 50 mg testosterone propionate intramuscularly every two weeks for one year. RESULTS: An improvement in ESR, Dutch health assessment questionnaire, and pain was noted. In addition, 21% of patients treated with testosterone fulfilled the ACR improvement criteria after one year, versus only 4% of the placebo group. The treatment was well tolerated. CONCLUSIONS: Testosterone may improve the general wellbeing of postmenopausal women with active rheumatoid arthritis.